Mengembangkan Kompetensi Sadar Lingkungan dan Keberlanjutan Melalui Aksi Kolaboratif Bersama Organisasi Masyarakat Sipil - Luerdi, Luerdi; Sahfida, Asmi Miftah; Anwar, Lutfiah Muthi; Andrestha, Alfina (Ragom Jurnal Pengabdian Masyarakat, 2025)
Ecological and sustainability awareness are emerging as new competencies among citizens, in line with the rise of environmental issues as both global and local concerns. Students, especially those studying International Relations, learn about environment-related topics and sustainability through formal classroom education. The issue is that they may have enough knowledge but lack experience in how environments and sustainability are promoted in real life or at the local level. It is necessary to connect theories and practices through an internship at a non-governmental organization specializing in environment and sustainability. This program involved the students of International Relations at Universitas Lampung and its partner, Wahana Lingkungan Hidup (Walhi), aiming to develop ecological and sustainability awareness along with practical skills, enabling them to observe and participate in environmental and sustainability projects and interact with stakeholders. This program was expected to benefit participants, partner, and the higher education institution, strengthening partnerships and collaboration in addressing common challenges.